Optical Logic Operation Encryption on ZnTe Flake. Issue 16 (29th May 2022) - Li, Dongyan; Li, Zexin; Chen, Ping; Pi, Lejing; Wang, Haoyun; Zhou, Xing; Zhai, Tianyou
Abstract: Logic operation encryption is emerging as a novel cryptographic mode, protecting logic operation from being attacked and tampered, and is a modern extension of conventional encryption system. However, the existing encryption methods are not conducive to the logic operation encryption due to the complexity, signal mode, and non‐adjustability of their design. Herein, an advanced logic operation encryption method is designed via the photoluminescence ratio of ZnTe, and the electrically and optically switchable NAND (Not AND) and NOR (Not OR) encryption based on this method is implemented. Two photoluminescence emissions can be selectively regulated by the gate voltage and excitation laser based on the different responses of band‐edge emission and defect emission. This novel approach will shed light on the development of high‐security encryption and computer information protection. Abstract : An electrically and optically switchable logic operation encryption based on the photoluminescence (PL) ratio of ZnTe is developed. Two PL emissions can be selectively regulated by the electric and optical fields due to different responses of band‐edge emission and defect emission. This work provides a design for the creation of logic operation encryption and holds great promise for high‐security encryption.